2014
DOI: 10.2522/ptj.20120443
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, Benefits, and Strategies for Physical Activity in Patients With Schizophrenia

Abstract: In accordance with patients' perceptions, there may be biopsychosocial determinants of physical activity behavior that are unique for this group of patients. Future studies should investigate whether physical activity interventions for patients with schizophrenia benefit from individual analyses of barriers and reward for physical activity in combination with the use of tailored strategies such as personal support and activity planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 49 publications
6
92
0
1
Order By: Relevance
“…73 Motivational techniques such as family member or caretakers involvement and customization of the exercise 77 might improve adherence of the patients 66,78 and highlighted the relationship between motivation, awareness of exercise benefits and self-efficacy. 77,79 Another potential limitation is that no significant baseline differences between patients and controls in FA were found. Although this is consistent with some earlier studies, 80,81 in a meta-analysis of DTI studies FA was lower in patients.…”
Section: Discussionmentioning
confidence: 99%
“…73 Motivational techniques such as family member or caretakers involvement and customization of the exercise 77 might improve adherence of the patients 66,78 and highlighted the relationship between motivation, awareness of exercise benefits and self-efficacy. 77,79 Another potential limitation is that no significant baseline differences between patients and controls in FA were found. Although this is consistent with some earlier studies, 80,81 in a meta-analysis of DTI studies FA was lower in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly reported motivators include weight management, social interaction, and the potential to improve energy levels 225,230 . Those who participate in exercise programs identify a socially inclusive environment 222,223 , low cost with transport provided 222 , social support 227,229 or incorporating a "buddy" system 234,244 , sessions in small groups with a friendly instructor 230,247 , and tailoring to individual preferences and ability 228,236 , as enablers to participation. Reports of helpful personal strategies for engaging in activity include, positive self-talk, avoiding too many activities in the day to prevent stress, and walking alone while listening to music 229 .…”
Section: Physical Activity Attitudes and Preferences Of Adults With Mmentioning
confidence: 99%
“…Most of these studies had a sample size of 34 or less [222][223][224][225][226][227][228][229][230][231][232][233][234][235][236][237][238]241 ; larger studies had sample sizes ranging between 52 and 138 239,240,242,243 . Common constructs on which these studies have reported, include:…”
Section: Physical Activity Attitudes and Preferences Of Adults With Mmentioning
confidence: 99%
See 2 more Smart Citations